2018
DOI: 10.1101/490706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinoid X receptor alpha is a spatiotemporally-specific therapeutic target for doxorubicin-induced cardiomyopathy in adult zebrafish

Abstract: While the genetic suppressor screen is efficient in suggesting therapeutic genes, this strategy has yet to be successful for cardiomyopathies in vertebrates. To develop such a strategy, we recently established a mutagenesis screen platform in zebrafish for systematic discovery of genetic modifiers of doxorubicin-induced cardiomyopathy (DIC). Here, we further revealed both molecular and cellular insights of the first salutary modifier emerged from the screen, i.e. gene-breaking transposon (GBT) 0419 that affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Thus, a major novelty of this study is to combine the power of zebrafish genetics and a human GWAS for both identification and functional elucidation of MAP7D1 as a clinically relevant susceptibility gene to DIC and heart failure. The feasibility of this approach was further supported by recent studies that reported RXRA as a genetic factor associated with anthracycline-induced cardiotoxicity (AIC) [13,15]. This approach, we believe, can be readily applied to study other AIC genes as well.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, a major novelty of this study is to combine the power of zebrafish genetics and a human GWAS for both identification and functional elucidation of MAP7D1 as a clinically relevant susceptibility gene to DIC and heart failure. The feasibility of this approach was further supported by recent studies that reported RXRA as a genetic factor associated with anthracycline-induced cardiotoxicity (AIC) [13,15]. This approach, we believe, can be readily applied to study other AIC genes as well.…”
Section: Discussionmentioning
confidence: 68%
“…Echocardiography. Echocardiography measurement was carried out using the Vevo 3100 high-frequency imaging system equipped with a 50 MHz (MX700) linear array transducer (FUJIFILM VisualSonics Inc.) accordingly [15]. Briefly, adult zebrafish at appropriate stages were anesthetized in tricaine (0.016%) for 5 minutes, placed ventral side up into a sponge.…”
Section: Determining Knockdown Efficiencymentioning
confidence: 99%
See 1 more Smart Citation